2015
DOI: 10.1093/rheumatology/kev036
|View full text |Cite
|
Sign up to set email alerts
|

Longer duration of B cell depletion is associated with better outcome

Abstract: Cycles of BCD that induce longer duration of BCD are associated with better outcome. Lymphopenia may help to predict longer duration of the depletion and better outcome, although the mechanism is unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…The Lupus Nephritis Assessment with Rituximab (LUNAR) study, the largest randomized trial of rituximab for the treatment of lupus nephritis to date, failed to demonstrate increased efficacy of rituximab despite achieving B cell depletion to the target of ,20 cells/ml in peripheral blood (10). Further characterization of the effects of rituximab in mouse models of lupus nephritis and patients with SLE has revealed that rituximab does not consistently result in complete or prolonged depletion of peripheral blood B cells and that lymphoid tissue B cell depletion may be incomplete as well (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Incomplete peripheral blood B cell depletion has been associated with a lack of response to rituximab in patients with SLE (20) and it is hypothesized that a lack of complete peripheral depletion in peripheral blood and/or the kidney tubulointerstitium may attenuate the efficacy of rituximab in lupus nephritis (22).…”
Section: Introductionmentioning
confidence: 99%
“…The Lupus Nephritis Assessment with Rituximab (LUNAR) study, the largest randomized trial of rituximab for the treatment of lupus nephritis to date, failed to demonstrate increased efficacy of rituximab despite achieving B cell depletion to the target of ,20 cells/ml in peripheral blood (10). Further characterization of the effects of rituximab in mouse models of lupus nephritis and patients with SLE has revealed that rituximab does not consistently result in complete or prolonged depletion of peripheral blood B cells and that lymphoid tissue B cell depletion may be incomplete as well (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Incomplete peripheral blood B cell depletion has been associated with a lack of response to rituximab in patients with SLE (20) and it is hypothesized that a lack of complete peripheral depletion in peripheral blood and/or the kidney tubulointerstitium may attenuate the efficacy of rituximab in lupus nephritis (22).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies focused on the use of RTX in autoimmune diseases have shown that the longer duration of B cell 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 depletion achieved, the better is the clinical response to the drug (36); despite also in SLE a deep depletion has been found as associated to clinical response (37), the proportion of patients achieving it is lower and the timing of repopulation quicker (38). Several factors have been considered responsible, such as, the presence or development of human anti-chimeric antibodies (HACAs) (39,40) as well as differences in terms of RTX clearance (41) as a consequence of a different immunoglobulin metabolism.…”
Section: Sle Has a Huge Variability In Terms Of Clinical Profiles Andmentioning
confidence: 99%
“…The renal response was typically positive and the adverse eventsevent rate was relatively low, especially in the context of a population mainly characterized by a relapsing course of the disease and exposure to several immunosuppressive drugs. Only one study (2326) reported the outcome of four patients treated with pre-emptive multiple administrations of RTX; interestingly, no flares were observed in this 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Table 1 a positive response rate was observed in 67% of the population at 6 and 12 months with improvements in proteinuria (4.41 g baseline vs 1.31 g post therapy, p=0.006) and serum albumin level (28.55 g baseline vs 36.46 g post therapy, p<0.001) (2629).…”
Section: Introductionmentioning
confidence: 95%
“…Our laboratory has shown that the frequency and/or function of Bregs, as assessed in in vitro studies, appears to be important in both RA 43 and SLE 44 . However, to our knowledge as discussed in previous sections, better clinical response to rituximab is observed in patients with RA and SLE who achieve complete and durable B-cell depletion and poor response is associated with incomplete B-cell depletion 37,45 . In RA, clinical response to rituximab appears to relate to the degree of B-cell depletion 46 and that poor clinical response to rituximab may be improved by delivering an extra dose of rituximab 47 .…”
Section: Rituximab Resistance Vs Refractory Diseasementioning
confidence: 86%